2004
DOI: 10.1002/jbm.a.30033
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin release from two‐solution and powder–liquid poly(methyl methacrylate)‐based bone cements by using novel pH method

Abstract: The release of gentamicin as a function of time was measured for Palacos and two-solution bone cements by using a novel pH technique. The pH of an aqueous solution of gentamicin is a function of the gentamicin concentration and it decreases linearly over concentrations of 0.0-0.1 wt %. Therefore, a new, direct, and inexpensive in vitro technique was developed based on continuous readings of the pH in phosphate-buffered saline (PBS) at 37 degrees C to determine the release kinetics of gentamicin from poly(methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…At early time points (<∼3 h), the amount of gentamicin eluted (cumulative and mass percentage) from Palacos R+G specimens immersed in PBS at 37°C was significantly higher when the test solution was magnetically stirred than when it was static but there was no significant difference between the two conditions in the total amount eluted after 24 h 66. This trend suggests that a higher rate of release of the antibiotic from the specimen surface is stimulated by making a homogeneous concentration of the gentamicin in the case of the stirred solution.…”
Section: In Vitro Elution Kineticsmentioning
confidence: 93%
See 1 more Smart Citation
“…At early time points (<∼3 h), the amount of gentamicin eluted (cumulative and mass percentage) from Palacos R+G specimens immersed in PBS at 37°C was significantly higher when the test solution was magnetically stirred than when it was static but there was no significant difference between the two conditions in the total amount eluted after 24 h 66. This trend suggests that a higher rate of release of the antibiotic from the specimen surface is stimulated by making a homogeneous concentration of the gentamicin in the case of the stirred solution.…”
Section: In Vitro Elution Kineticsmentioning
confidence: 93%
“…When mixed, the two solutions polymerize via a free radical reaction. Relative to Palacos R‐40 loaded with 0.5 g of gentamicin, a lower percentage of gentamicin eluted from specimens of a two‐solution cement loaded with the gentamicin (in amounts either equivalent to the concentration in Palacos R‐G or twice that concentration) when immersed in PBS at 37°C, over a period of 24 h. This trend is a consequence of the fact that, compared to the gentamicin‐loaded Palacos R‐40 specimens, the two‐solution cement specimens had lower bulk porosity, a higher molecular weight of the polymerized matrix, lower concentration of the radiopacifier in the cement matrix, and lower absorption of water 66…”
Section: In Vitro Elution Kineticsmentioning
confidence: 99%
“…5). This pattern of elution is typical for ''low-dose'' and ''medium-dose'' (antibiotic loading between 5 wt/wt% and 10 wt/wt%) ALBC formulations [7,10,24]. The best-fit relationships between the concentration of the eluted daptomycin (CON) and t (over the time range 1 day B t B 7 days) (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Based on the results of initial cultures, vancomycin, 1 g, tobramycin, 2.4 g, or iminipenem alone or in combination are used per packet of Palacos R (Zimmer, Warsaw, Indiana) polymer to form the beads or spacers. In several studies, Palacos R demonstrated an increased elution of antibiotics when compared with other formulations of PMMA [54][55][56][57]. In the foot and ankle, antibiotic-impregnated PMMA spacer blocks are preferable to beads to fill the osseous void created by the projectile and to hold the soft tissues at normal tension.…”
Section: Antibiotic Impregnated Beads and Spacersmentioning
confidence: 98%